Podcast dalam Chanel Youtube Hidayatullah Tv Menjadi Sumber Pengajaran, Sumber Belajar dan sebagai Persiapan Contributor Mualaf - Alwazir Abdusshomad (LP2M STIT Palapa Nusantara, 2022)
This study aims to determine the relevance of Podcasts in the Hidayatullah TV Youtube Chanel as a source of teaching, learning resources and as a preparation for converts to converts. The research used is qualitative with primary sources in the form of 3 (three) Video Podcasts on Chanel Hidayatullah TV, namely (1) Video with the title